2022
DOI: 10.29408/jel.v8i1.4569
|View full text |Cite
|
Sign up to set email alerts
|

Developing interactive e-module based on realistic mathematics education approach and mathematical literacy ability

Abstract: Teaching and learning activities are carried out online during the pandemic situation. This condition makes the teaching and learning process in the classroom requires teaching materials that can support the learning process. However, some teachers still use teaching materials commonly used during face-to-face learning, which is irrelevant for offline learning. Therefore, teachers need alternative interactive teaching materials that can facilitate online learning. This study aims to produce teaching materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Additionally, the three models described above were developed in secondary schools and colleges, while learning models aimed at improving mathematical literacy have yet to be developed in elementary schools. Aside from learning models, other products such as web-based RME (Lisnani et al, 2023) and learning modules based on RME (Aulia & Prahmana, 2022;Mattoliang et al, 2022;Yuliana et al, 2023) have also shown effectiveness in increasing students' mathematical literacy.…”
Section: Product Testing Stagementioning
confidence: 99%
“…Additionally, the three models described above were developed in secondary schools and colleges, while learning models aimed at improving mathematical literacy have yet to be developed in elementary schools. Aside from learning models, other products such as web-based RME (Lisnani et al, 2023) and learning modules based on RME (Aulia & Prahmana, 2022;Mattoliang et al, 2022;Yuliana et al, 2023) have also shown effectiveness in increasing students' mathematical literacy.…”
Section: Product Testing Stagementioning
confidence: 99%
“…By forming their knowledge, students will have an impression of the learning material, and it will be easier to understand the material they are studying. The learning process requires teaching materials that can support learning in the classroom (Aulia & Prahmana, 2022;Iba'd & Pahlevi, 2020). A lecturer developing teaching materials requires cognitive abilities to analyze the curriculum, indicators and learning objectives (Prihandoko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Genc and Erbas (2019) and Pugalee (1999) research results show that mathematical literacy can improve higher-order mathematical thinking skills, including mathematical reasoning abilities. Aulia and Prahmana (2022) and Nursakiah et al (2022) show that e-module with mathematical literacy can improve students' abilities.…”
Section: Introductionmentioning
confidence: 99%